Foreign Direct Investment : issues in measurement and analysis - O'Mahony, Clare (Trinity College (Dublin, Ireland). Trinity Business School, 2015)
This thesis consists of three empirical studies exploring issues in the measurement and analysis of Foreign Direct Investment (FDI). The 'classical form' of FDI is of greenfield, direct one-to-one investment from multinational parent to affiliate in manufacturing industry. The first study highlights the growing significance of financial services FDI, Special Purpose Entities (SPEs), and pass-through investment, and that the nature of FDI has evolved from its classical form to encompass other types of foreign investment. The other two studies explore two forms of FDI at two points along this evolutionary path. The second study focuses on classical FDI in Ireland prior to EU entry while the third study explores venture capital (VC) in Ireland, which is heavily internationalised and, as such, constitutes a 'newer' form of FDI. Ireland is centrally located in many of the changes that have taken place globally in the FDI landscape and, as a late industrialiser and a major recipient of FDI, its experience is of widespread interest to scholars and policymakers.
Keywords: Business, Ph.D.; Ph.D. Trinity College Dublin.